Proceedings of the Second International Conference on Computer and Communication Technologies IC3T 2015, Volume 2 - Satapathy, Suresh Chandra; Raju, K. Srujan; Mandal, Jyotsna Kumar; Bhateja, Vikrant; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2016)
The book is about all aspects of computing, communication, general sciences and educational research covered at the Second International Conference on Computer & Communication Technologies held during 24-26 July 2015 at Hyderabad. It hosted by CMR Technical Campus in association with Division - V (Education & Research) CSI, India. After a rigorous review only quality papers are selected and included in this book. The entire book is divided into three volumes. Three volumes cover a variety of topics which include medical imaging, networks, data mining, intelligent computing, software design, image processing, mobile computing, digital signals and speech processing, video surveillance and processing, web mining, wireless sensor networks, circuit analysis, fuzzy systems, antenna and communication systems, biomedical signal processing and applications, cloud computing, embedded systems applications and cyber security and digital forensic. The readers of these volumes will be highly benefited from the technical contents of the topics.
Chapter 1. Human Gait Recognition Using Gait Flow Image and Extension Neural Network -- Chapter 2. Enhanced Topology Preserving Maps for Wireless Sensor Network through D-VCS -- Chapter 3. Real-time Processing and Analysis for Activity Classification to Enhance Wearable Wireless ECG -- Chapter 4. Adaptive Video Quality Throttling Based on Network Bandwidth for Virtual Classroom Systems -- Chapter 5. Efficiency-Fairness Trade-Off Approaches For Resource Allocation In Cooperative Wireless Network -- Chapter 6. An Enhanced Security Pattern for Wireless Sensor Network -- Chapter 7. Honey Pot: A Major Technique for Intrusion Detection -- Chapter 8. Computational Intelligence Based Parameterization on Force Filed Modeling for Silicon Cluster Using ASBO -- Chapter 9. Natural Language Based Self Learning Feedback Analysis System -- Chapter 10. Adaptive Filter Design for Extraction of Fetus ECG Signal -- Chapter 11. Improving Query Processing Performance Using Optimization Techniques for Object Oriented DBMS -- Chapter 12. Linear and Non Linear Buckling Testing on Aluminium Structures -- Chapter 13. A Performance Analysis of Open Stack Open-source Solution for IaaS Cloud Computing -- Chapter 14. The Application of Sub-pattern Approach in 2D Shape Recognition and Retrieval -- Chapter 15. A Data Driven Approach for the Option Pricing Algorithm -- Chapter 16. Moderator Intuitionistic Fuzzy Sets and Application in Medical Diagnosis -- Chapter 17. An Empirical Comparative Study of Novel Clustering algorithms for Class Imbalance Learning -- Chapter 18. Augmenting Women's Safety-In-Numbers in Railway Carriages with Wireless Sensor Networks -- Chapter 19. Analysis of Student Feedback by Ranking the Polarities -- Chapter 20. Seizure Onset Detection by Analyzing Long Duration EEG Signals -- Chapter 21. Enhancing the Performance of Map Reduce DefaultScheduler by Detecting Prolonged Task Trackers in Heterogeneous Environments -- Chapter 22. Prototype of a Coconut Harvesting Robot with Visual Feedback -- Chapter 23. Suppression of Impulse Noise in Digital Images Using Hermite Interpolation -- Chapter 24. Wireless Personal Area Network and PSO Based Home Security System -- Chapter 25. A Framework for Ranking Reviews Using Ranked Voting Method -- Chapter 26. Multilevel Thresholding Segmentation Approach Based on Spider Monkey Optimization Algorithm -- Chapter 27. Dynamic Multiuser Scheduling with Interference Mitigation in SC-FDMA Based Communication Systems -- Chapter 28. Design of Proportional-Integral-Derivative Controller Using Stochastic Particle Swarm Optimization Technique for single Area AGC including SMES and RFB units -- Chapter 29. A Enhanced Micro strip Antenna Using Metamaterial at 2.4 GHz -- Chapter 30. Adaptive MAC for Bursty Traffic in Wireless Sensor Networks -- Chapter 31. Secured Authentication and Signature Routing Protocol for WMN (SASR) -- Chapter 32. A Minimal Subset of Features Using Correlation Feature Selection Model for Intrusion Detection System -- Chapter 33. Analysis of Single Layered Multiple Aperture Shield for Better Shield Effectiveness -- Chapter 34. MRI Classification of Parkinson's Disease Using SVM and Texture Features -- Chapter 35. Variational Mode Feature Based Hyperspectral Image Classification -- Chapter 36. Implementation Of Fuzzy Based Robotic Path Planning -- Chapter 37. Texture Segmentation by a New Variant of Local Binary Pattern -- Chapter 38. Integrating Writing Direction and Handwriting Letter Recognition in Touch Enabled Devices -- Chapter 39. A New Approach for Single Text Document Summarization -- Chapter 40. Analysis, Classification and Estimation of Pattern for Land of Aurangabad Region Using High Resolution Satellite Image -- Chapter 41.A Novel Fuzzy Min Max Neural Network and Genetic Algorithm Based Intrusion Detection System -- Chapter 42. Real Time Fault Tolerance Task Scheduling Algorithm with Minimum Energy Consumption -- Chapter 43. Completely Separable Reversible Data Hiding with Increased Embedding Capacity Using Residue Number System -- Chapter 44. A Metric for Ranking the Classifiers for Evaluation of Intrusion Detection System -- Chapter 45. Analysis of Different Neural Network Architectures in Face Recognition System -- Chapter 46. A Novel Approach for Diagnosis of Noisy Component in Rolling bearing Using Improved Empirical Mode Decomposition -- Chapter 47. A Novel Solution of Dijkstra's Algorithm for Shortest Path Routing with Polygonal Obstacles In Wireless Networks Using Fuzzy Mathematics -- Chapter 48. Asymmetric Coplanar Waveguide fed Monopole Antenna with SRR in the Ground Plane -- Chapter 49. Image processing of Natural Calamity Images Using Healthy Bacteria Foraging Optimization Algorithm -- Chapter 50. Necessitate Green Environment for Sustainable Computing -- Chapter 51. Determinantal Approach to Hermite-Sheffer Polynomials -- Chapter 52. Intelligent Traffic Monitoring System -- Chapter 53. Analysis of Mining, Visual Analytics Tools and Techniques in Space and Time -- Chapter 54. Dimensionality reduced Recursive Filter features for hyperspectral classification -- Chapter 55. Customized Web User Interface for Hadoop Distributed File System -- Chapter 56. Reinforcing Web Accessibility for Enhanced Browsers and Functionalities according to W3C Guidelines -- Chapter 57. Feature and Search Space Reduction for Label Dependent Multi-label Classification -- Chapter 58. Link Expiration Based Routing in Wireless Ad hoc Networks -- Chapter 59. Analysis of Dual Beam Pentagonal Patch Antenna -- Chapter 60. Combination of CDLEP and Gabor features for CBIR -- Chapter 61.Scheduling Real Time Transactions Using Deferred Pre-emptive Technique -- Chapter 62. An Intelligent Packet Filtering Based on Bi-Layer Particle Swarm Optimization with Reduced Search Space -- Chapter 63. Storage Optimization of Cloud Using Disjunctive Property of p -- Chapter 64. Co-Training with Clustering for the Semi Supervised Classification of Remote Sensing Images -- Chapter 65. An Integrated Secure Architecture for IPv4/IPv6 Address Translation between IPv4 and IPv6 Networks -- Chapter 66. Logistic Regression Learning Model for Handling Concept Drift with Unbalanced Data in Credit Card Fraud Detection System -- Chapter 67. Music Revolution through Genetic Evolution Theory -- Chapter 68. Low-Cost Supply Chain Management and Value Chain Management with Real-time Advance Inexpensive Network Computing -- Chapter 69. Opinion classification Based on Product Reviews from an Indian e-commerce Website -- Chapter 70. Mitigation of Fog and Rain Effects in Free Space Optical Transmission Using Combined Diversity -- Chapter 71. Technology Involved in Bridging Physical, Cyber and Hyper World -- Chapter 72. Cloud Load Balancing and Resource Allocation -- Chapter 73. A Novel Methodology to Filter out Unwanted Messages from OSN user's Wall Using Trust Value Calculation -- Chapter 74. Resource Prioritization Technique in Computational Grid Environment -- Chapter 75. Fuzzy-Based M-AODV Routing Protocol in MANETs -- Chapter 76. Cuckoo Search in Test Case Generation and Conforming Optimality Using Firefly Algorithm -- Chapter 77. Time Domain Analysis of EEG to Classify Imagined Speech -- Chapter 78. Accurate Frequency Estimation Method Based on Basis Approach and Empirical Wavelet Transform -- Chapter 79. Hybrid Recommender System with Conceptualization and Temporal preferences -- Chapter 80. An Approach to Detect Intruder in Energy Aware Routing for Wireless MeshNetworks.
Keywords: Telecommunication; Computational intelligence; Signal processing; Computer networks .; Communications Engineering, Networks; Computational Intelligence; Signal, Speech and Image Processing; Computer Communication Networks